Fatigue Resistance of Cast-on Implant Abutment Fabricated with Three Different Alloys - Puengpaiboon, Usanee; Didron, Pavinee Padipatvuthikul (European Journal of Dentistry, 2022)
Objectives This study aimed to evaluate fatigue resistance of cast-on implant abutment using three alloys.Materials and Methods Forty specimens of implant-supported crowns were prepared; Group 1 (TA) stock titanium abutments, Group 2 (GS) abutment cast with 40% gold alloy, Group 3 (GP) abutment cast with palladium alloy, and Group 4 (CN) abutment cast with nickel–chromium alloy. Specimens were cyclic loaded at 20 Hz, starting from 200 N (5,000 cycles), followed by stepwise loading of 400, 600, 800, 1,000, 1,200, 1,400, 1,600, and 1,800 N (30,000 cycles/step). Specimens were loaded until failure or reached 245,000 cycles.Statistical Analysis The withstand cycles were analyzed using one-way analysis of variance and Weibull survival analysis. Fracture surfaces were examined using scanning electron microscopy.Results The results of withstand cycles were TA (189,883 ± 22,734), GS (195,028 ± 22,371), GP (187,662 ± 22,555), and CN (200,350 ± 30,851). The statistical analysis showed no significant difference between the groups (p = 0.673).Conclusion Although CN has higher Weibull characteristic strength which means greater durability, its lower Weibull modulus demonstrated less structural reliability. Consistent failures at implant fixture level were also found in CN group.
Keywords: dental implant; cast-on abutment; fatigue resistance; mechanical failure